Toleransi, pluralisme, dan multikulturalisme di indonesia: Tantangan dan implementasinya dalam kehidupan sosial di era digital - Dinanti, Keysha Amalia (Maliki Interdisciplinary Journal, 2026)
Indonesia is a multicultural country with very high diversity in ethnicity, religion, culture, and language. This condition makes the values of tolerance, pluralism, and multiculturalism important foundations in maintaining social harmony within a diverse society. However, the development of the digital era and social media has brought significant changes to patterns of social interaction in society. These changes not only have positive impacts but also present various new challenges in social life. This study aims to analyze the challenges and implementation of the values of tolerance, pluralism, and multiculturalism in Indonesia in the digital era. The method used is a literature study with a descriptive qualitative approach through the review of relevant scientific literature. The findings show that the digital era is characterized by the increasing spread of misinformation, hate speech, intolerance, and social polarization that can disrupt social harmony in society. Strengthening digital literacy, multicultural education, and religious moderation are important steps in maintaining social cohesion in Indonesia. These efforts are necessary to ensure that the value of tolerance is preserved and able to adapt to the increasingly complex development of society in the digital era.